Fallacy of wide undrained strength range at the Casagrande liquid limit. Issue 3 (13th March 2019) - O'Kelly, Brendan C
Abstract : The liquid limit (LL), as originally proposed by Atterberg, is notionally the water content below which fine-grained soil ceases to flow as a liquid. In many countries, the Casagrande-cup approach is the standard procedure for LL determinations. For remoulded fine-grained soil, the undrained shear strength ( s u(LL) ) corresponding to the Casagrande LL water content ( w L(cup) ) value can range 0·7–3·9 kPa, but typically 1·0–2·7 kPa, with many researchers agreeing on a value of around 1·6–1·7 kPa. Further, the values of w L(cup), as determined using standard-compliant Casagrande-cup devices, correspond to a specific strength value of ∼1·0 m 2 /s 2, such that the value of s u(LL) reduces with increasing w L(cup) . A few research papers have, however, reported significantly higher s u(LL) values (>4 kPa and up to 12 kPa) for some fine-grained soils investigated. This paper critiques these experimental data and debunks this myth by first considering how these superhigh s u(LL) values were deduced and then explaining why they are not correct. For low- to very high-plasticity soils, the overwhelming weight of experimental evidence presented indicates that s u(LL) can range 1–3 kPa and typically decreases from approximately 2·5 to 1·6 kPa for w L(cup) increasing from 20 to 70%.